061 Ocrelizumab reduces disability progression independent of relapse activity in patients with relapsing multiple sclerosis (RMS) (ENCORE). Issue 6 (24th May 2018) - Kappos, Ludwig; Wolinsky, Jerry S; Giovannoni, Gavin; Arnold, Douglas L; Lublin, Fred; Wang, Qing; Model, Fabian; Wei, Wei; Garren, Hideki; Manfrini, Marianna; Belachew, Shibeshih; Hauser, Stephen
Abstract : Introduction: Ocrelizumab-(OCR) showed superior efficacy vs interferon beta-1a-(IFNβ1a) in OPERA I/II trials in RMS. Confirmed disability progression-(CDP) based on composite of Expanded Disability Status Scale-(EDSS), timed 25-foot walk-(T25FW) and 9-hole peg test-(9HPT) may better characterise aspects of disability progression than EDSS alone and has improved sensitivity for assessing progression in secondary progressive MS-(SPMS). Methods: RMS patients, including relapsing SPMS patients, in OPERA I/II-(NCT01247324 /NCT01412333) received IV-OCR 600 mg (q24w) or SC-IFNβ1a 44 µg (tiw) over 96 weeks. CCDP was defined as disability progression measured by EDSS (increase ≥1.0 or 0.5 if baseline >5.5) or ≥20% T25FW increase or ≥20% 9 HPT increase, confirmed after ≥12/≥24 weeks. Definition-1 of CCDP-IRA=reference EDSS/T25FW/9HPT was re-baselined at first available assessment ≥30 days, after each relapse and no relapse should occur between baseline and initial disability progression [IDP], and within 30 days post-IDP and 30 days prior to IDP confirmation. Definition-2=period of no relapse for 30 days post-IDP confirmation. Subgroup analysis included patients at potentially higher SPMS risk based on baseline-EDSS ≥4.0 and pyramidal Kurtzke Functional Systems Score ≥2. Results: In the pooled intention-to-treat (ITT) cohort (n=1, 656), risk reduction (RR; OCR vs IFNβ1a) for 12-/24 week CCDP was 34% (30.7% vs 21.5%; p<0.001) and 31% (22.6% vs 16.1%; p=0.002). The 12-/24 week CCDP-IRA RRs for Definition-1 were 24% (25.4% vs 19.6%; p=0.010) and 22% (19.2% vs 14.9%; p=0.046); and for Definition-2, 25% (25.4% vs 19.5%; p=0.008) and 23% (19.2% vs 14.8%; p=0.039). In the subgroup at higher SPMS risk, 12-/24 week RRs for CCDP-IRA (Definition-2) were 40% (31.2% vs 19.1%; p=0.022) and 36% (26.9% vs 16.6%; p=0.064). All CCDP-IRA components in the ITT and subgroups followed similar trends. Conclusion: Results show that considerable disability progression in RMS occurs independently of protocol-defined relapses. Ocrelizumab significantly reduced progression vs IFNβ1a in the OPERA ITT population of RMS patients and more so in the subgroup at higher SPMS risk.